The Reality of Educational Supervision in the Schools of Ramallah and Al- Bireh Governorate from the School Principals Point of View - Abu Khayran, Ashraf Mohammad; Rantisi, Nancy Rimon (Journal of Educational and Psychological Sciences, 2023)
The study aims to invistigate The Reality of Educational Supervision in Ramallah and Al-Bireh Governorate from the School Principals Point of View, and the differences in each of them due to: gender, supervising authority, educational qualification, and years of experience. The study uses the relational descriptive approach, by applying: The educational supervision and outstanding performance of teachers. These scale is applied to a stratified random sample, which includes 163 principals in the academic year 2021-2022. The results show the mean of the reality of educational supervision of teachers, with an average of 3.63, and a percentage 72.6%, and "the roles of the educational supervisor" is the highest. On the other hand, "the supervisory tasks" is the lowest, and the results indicate that there is no statistically significant difference between the educational supervision of teachers averages and their domains due to the variables: gender, supervising authority, educational qualification, and years of experience.